Self-Efficacy, Dietary Adherence, and Medication Compliance among Hypertension Patients. - Andayani, Sri Astutik; Sholehah, Baitus; Kamaruzzaman, Muh. (Fakultas Kesehatan, Universitas Nurul Jadid, 2024)
Introduction: Hypertension is a significant non-communicable disease that is a global health priority due to its status as a major risk factor for cardiovascular conditions such as stroke, heart failure, and myocardial infarction. A lack of public awareness regarding the detrimental effects of hypertension remains a critical issue, compounded by non-compliance with dietary and medication regimens, which exacerbates the condition of hypertensive patients. Objectives: This study aims to identify the factors influencing dietary adherence and medication compliance among hypertensive patients. Methods: A cross-sectional design was employed in this study, which focused on hypertensive patients from Alasbayur Village and Campoan Village, totaling 500 individuals. Using the Slovin formula, a sample of 222 participants was selected. Data were collected through a closed questionnaire, where respondents indicated their answers by marking their responses. Data analysis included bivariate analysis using the Spearman test and multivariate analysis using logistic regression. The research was conducted between March and April 2023. Results: Among the factors tested, four independent variables were significantly associated with adherence to diet and medication: perceived severity (P = 0.005), perceived benefits (P = 0.017), cues to action (P = 0.019), and self-efficacy (P = 0.021). Two variables showed no significant association: perceived vulnerability (P = 0.34) and perceived barriers (P = 0.165). Conclusions: The study identifies four variables that are significantly related to dietary adherence and medication compliance in hypertension patients. Conversely, perceived vulnerability and perceived barriers are not significantly associated with adherence, suggesting that other factors may influence these behaviors.